Problematika Pasal Karet dalam UU ITE dan Implikasinya terhadap Kebebasan Berekspresi: Sebuah Tinjauan Kritis dari Perspektif Negara Hukum Demokratis - Gilang Rizki Aji Putra (BULETIN ADALAH, 2021)
Ambiguous provisions in the Electronic Information and Transactions Law have created legal uncertainty and threatened freedom of expression. This article analyzes problematic “rubber articles,” particularly Articles 27 and 28, and their impact on Indonesia’s digital democracy. Using normative legal research with conceptual and statutory approaches, the study finds that unclear formulations violating lex certa enable excessive discretion and criminalization of critical expression. Their implementation produces a chilling effect, limiting public participation and weakening democratic discourse. Reformulating offenses and strictly applying ultimum remedium are essential to safeguard constitutional freedoms. Keywords: Electronic Transactions Law, Rubber Articles, Freedom of Expression, Lex Certa, Chilling Effect